Christification of the Least: Potential for Christology and Discipleship. (December 2018) - Miller, Liam
Abstract : This paper argues that the christification of the least should shape Christology and subsequently Christian discipleship. Christification is articulated as the process by which individuals or groups, inside or outside the church and marked by displacement, marginalisation or persecution, are recognised as bearing Christ's presence in a special way. Those christified share in Christ's revelatory, soteriological and sanctifying role for the community who encounter, serve and learn from them. This illuminates the ethical and missional impact of christification. Taking Jon Sobrino's argument that Christology must take into account the historically received texts about Christ and the reality of Christ in the present, I argue that Christology cannot be complete without a transformative encounter with the christified least. For those in places of privilege, Christologies employing christification have an immediate effect on discipleship, locating the presence of Christ in the least amongst their community. For the marginalised, christification grants agency; seen as the embodiment of Christ, they facilitate revelation and shape ethical engagement. Attention is paid throughout the paper to how christification, as modelled particularly by theologians writing from or for marginalised or migrant communities, could be applied to my own Australian context, particularly current debates around refugees and Indigenous peoples.